Efficacy of Simvastatin on Chronic Renal Failure Patients - A Spectroscopic Approach - GUNASEKARAN, S.; RENUGA DEVI, T.S.; SAKTHIVEL, P.S. (Asian Journal of Chemistry, 2010)
The effect of simvastatin in chronic renal failure patients spectroscopically is investigated. A total of 10 chronic renal failure patients were assigned to receive simvastatin (zocor) 20mg/d, added to their ongoing treatment, for 6 months. Blood samples were obtained at baseline and after 3 and 6 months of observation for the determination of their lipid profiles and study on biochemistry of blood using FTIR spectroscopy. The FTIR spectra of blood sera of the patients were recorded before and after drug therapy over the region 4000-400 cm-1. Simvastatin therapy reduced urea by 22%, LDL cholesterol by 21.5% and triglycerides by 25.7% and creatinine by 20%. These data suggest that in chronic renal failure patients, simvastatin profoundly affect the lipid profile, as well as the triglyceride levels.